A scoping review on flipped classroom approach in language education: challenges, implications and an interaction model. Issue 5 (4th July 2022) - Jiang, Michael Yi-chao; Jong, Morris Siu-yung; Lau, Wilfred Wing-fat; Chai, Ching-sing; Liu, Kelly Shu-xia; Park, Moonyoung
Abstract: The present work synthesizes the studies in flipped language education based on Social Sciences Citation Index publications up to the year 2018. A sum of 33 studies were finalized as the targeted studies and our research questions were formulated regarding (1) the overall trend and features of the existing studies, (2) their research foci, (3) the role of technology, and (4) the integration of FL/L2 learning and teaching theories, models or strategies into flipped classroom. Some research gaps were identified, including a bias toward outcome-oriented quantitative studies over process-oriented qualitative studies. Additionally, an overwhelming majority of the studies were conducted from the learners' perspectives, while few studies took the teachers' perspectives. More importantly, to guide the course design and implementation, the present review proposed a comprehensive 'interaction model' integrating four key elements into flipped FL/L2 education. The model featured two types of interaction, namely 'interaction with content' and 'interaction via content', highlighting the uniqueness of flipped FL/L2 education. The study incorporated learner preparedness in the interaction model, entailing a practical interface for the principle of 'design for failure', that is, predicting and preparing contingencies for the times when in-class interactions do not go as planned for technical or other reasons.